The Ultradiffuse Galaxy AGC 242019 with a Negative Metallicity Gradient - Junbao Ni; Yong Shi; Xin Li; Zhiyuan Zheng; Zhiyu Zhang; Xiaoling Yu; Fuyan Bian; Jianhang Chen; Junzhi Wang (The Astrophysical Journal)
The origin of ultradiffuse galaxies (UDGs) remains poorly understood. While the metallicity gradient can offer key clues about the formation mechanisms of UDGs, no such studies have been conducted for field UDGs. We carry out deep MUSE observations of one of the brightest UDGs in the H i —AGC 242019. With various strong emission-line metallicity calibrators, we found that this galaxy shows a negative metallicity gradient: $-0.08± 0.02\,{kpc}^{-1}/-0.30± 0.07\,R_{{\rm{e}}}^{-1}$ for N2S2H α metallicity calibrator and $-0.028± 0.006\,{kpc}^{-1}/-0.11\,± 0.02\,R_{{\rm{e}}}^{-1}$ for O3N2, with average metallicities of 7.6 ± 0.2 and 8.4 ± 0.1, respectively. By comparing with local dwarfs and spirals, we find that AGC 242019 shows a similar metallicity gradient to local dwarfs. This result suggests that AGC 242019 may not be the result of a dwarf that experiences very strong feedback.